Understanding Powerful IPS Learning - Ni Kadek Agustina (Social Studies Education Department, Faculty of Teacher Training and Education, Universitas Lambung Mangkurat, 2021)
Education has an essential role in the life of the nation and state which is usually held formally through educational institutions (schools), where students are community members who try to develop their potential through the available learning process educators/teachers as one component of education have a high responsibility because their role as educators determines changes that can bring the next generation of the nation to be virtuous, have a noble character, are intelligent, insightful, skilled and cultured. The teacher primarily determines the effectiveness of education. . Theoretical, independent social sciences are less flexible when applied in dealing with problems that exist in the realm of citizenship.,This study uses a qualitative descriptive approach to provide an understanding of powerful learning. To achieve the research objectives, data were collected through library studies, searching, collecting, and reading materials from journals, books, and sources related to the papers discussed. Learning must be integrated with the social sciences and no longer centered on the teacher. It should be taught independently and powerful, namely value-based learning, meaningful, integrated, challenging, and active.